British business in the formative years of European integration 1945-1973 - Rollings, Neil (Cambridge studies in the emergence of global enterprise, 2007)
This book questions conventional accounts of the history of European integration and British business. Integration accounts normally focus on the nation-state, while Neil Rollings focuses on business and its role in the development of European integration, which business historians have previously overlooked. Business provided a key link between economic integration, political integration, and the process of Europeanization. British businessmen perceived early on that European integration meant much more than the removal of tariffs and access to new markets. Indeed, British entry into the European community would alter the whole landscape of the European working environment. Consideration of European integration is revealed as a complex, relative, and dynamic issue, covering many issues such as competition policy, taxation, and company law. Based on extensive archival research, this book uses the case of business to emphasize the need to blend national histories with the history of European integration